Integration of Islamic Religious Education Values in Biology Subjects in High Schools - Maisaroh Maisaroh (Ruhama : Islamic Education Journal, 2022)
Islam has never dictated from science, it means that the value of Islamic religious education is found in various fields of study in every educational institution. Therefore, this study aims to reveal the form of Islamic religious education values contained in the field of biological studies. The research was conducted at SMA Negeri 1 Lembah Melintang, the approach used was descriptive qualitative, data was collected by observation, interviews and documentation studies. The result of the study is the integration of Islamic religious values with biology learning subjects starting from the learning planning process including the syllabus and learning implementation plan. The form of integration of Islamic religious education values includes the Islamic values of ilahiyah ubudiyah and ilahiyah muamalah which are used when students say greetings to teachers and include biology verses in the material. The recommendation of the results of this study is that every teacher in the field of general studies must improve the ability to integrate subjects with Islamic values.